Síndrome do intestino irritável - Machado, Wellington Monteiro [UNESP] (My University, 2000)
Irritable bowel syndrome is a high prevalent functional disorder. Its diagnosis is based in symptoms and the Rome Criteria. The treatment takes in account psychosocial and biologic factors. The therapeutic measures aim to correct the predominant symptoms: constipation, diarrhea and abdominal pain.
Irritable bowel syndrome
Keywords: Bowel; Gastrointestinal motility; Irritable bowel syndrome; Visceral sensitivity